Long-term Experience of Using of Polytetrafluoroethylene Orbital Implants - I. A. Filatova; S. A. Shemetov; I. M. Mohammad; Yu. P. Kondrateva (Oftalʹmologiâ, 2024)
Purpose: to evaluate the long-term results of using polytetrafluoroethylene orbital implants in patients with anophthalmos.Patients and methods. The clinical group consisted of 1560 patients with blind and unpromising eyes or anophthalmos, who were divided into 3 groups (I, II, and III) depending on the method of surgical treatment used — evisceration of the eye with posterior pole resection and neurectomy, enucleation of the eye, and plastic orbital socket surgery, respectively.Results. All patients in the study groups showed a positive result according to the criteria: stump mobility averaged (130,1°), prosthesis mobility averaged (106,6°), prosthesis entrapment after evisceration was less common than in patients after eye enucleation by 14.5 %. And the average value of the prosthesis sinking (mm) was lower by 78.0 %. Occlusion of the upper eyelid was also 16.7 % less common, and the average occlusion of the upper eyelid (mm) was 37.3 % lower. PTFE orbital implants have proven to be affordable, biocompatible and easy to use implants. The effect of the operation remained stable with long-term follow-up up to 15 years. There were no complications directly related to the use of PTFE orbital implants.